International Livestock Centre preserves Africa's declining wealth of animal biodiversity - Rege, J.E.O. (1994)
This paper discusses the research plan established to inventory and develop African breeds and protocols for In situ characterization. The paper also presents a review of West African Taurine cattle breeds. Minimum essential data set for breed characterization is summarised in a table form, and breed characterization activity schedule is presented for three regions, viz, Eastern Africa, Southern Africa, and West Africa.